Proceedings 6th Interaction and Concurrency Experience, ICE 2013, Florence, Italy, 6th June 2013 - Carbone, Marco; Lanese, Ivan; Lluch-Lafuente, Alberto; Sokolova, Ana (HAL CCSD, 2013)
International audience This volume contains the proceedings of ICE'13, the 6th Interaction and Concurrency Experience workshop, which was held in Florence, Italy on the 6th of June 2013 as a satellite event of DisCoTec'13. The ICE workshop series has a main distinguishing aspect: the workshop features a novel review and selection procedure. The previous editions of ICE were affiliated to ICALP'08 (Reykjavik, Iceland), CONCUR'09 (Bologna, Italy), DisCoTec'10 (Amsterdam, The Netherlands), DisCoTec'11 (Reykjavik, Iceland) and DisCoTec'12 (Stockholm, Sweden). The ICE procedure for paper selection allows PC members to interact, anonymously, with authors. During the review phase, each submitted paper is published on a forum and associated with a discussion forum whose access is restricted to the authors and to all the PC members not declaring a conflict of interests. The PC members post comments and questions that the authors reply to. As at the past five editions, the forum discussion during the review and selection phase of ICE'13 has considerably improved the accuracy of the feedback from the reviewers and the quality of accepted papers, and offered the basis for a lively discussion during the workshop. The interactive selection procedure implies additional effort for both authors and PC members. The effort and time spent in the forum interaction is rewarding for both authors ― when updating their papers ― and reviewers ― when writing their reviews: the forum discussion helps to discover and correct typos in key definitions and mispelled statements, to improve examples and presentation of critical cases, and solve any misunderstanding at the very early stage of the review process. Each paper was reviewed by three PC members, and altogether 6 papers were accepted for publication. We were proud to host two invited talks by Davide Sangiorgi and Filippo Bonchi, whose abstracts are included in this volume together with the regular papers. The workshop also featured a brief announcement of an already published paper. ...